Reflective practice and vocational training: theoretical approaches in the field of Health and Nursing - Netto,Luciana (2018)
Abstract Objective: Theoretical reflection that uses Reflexivity as a theoretical reference and its objective is to approach Donald Schön's reflective thinking, interrelating it with the innovative curriculum. Method: The writings of Schön and other authors who addressed the themes in their works were used. Results: The innovative curriculum as an expression of dissatisfaction with the fragmentation paradigm may favor reflective practice, since it is necessary to mobilize reflexivity for actions and contexts that are unpredictable in the field of health promotion. Conclusions: The innovative curriculum favors and is favored by a reflective practice and the development of competencies for the promotion of health. Implications for practice: The findings apply to the practice of nurses to deal with the conditioning and determinants of the health-disease process.